2022
DOI: 10.3390/polym14061091
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Ultraviolet Light Resistance of Colorless and Transparent Semi-Alicyclic Polyimide Nanocomposite Films via the Incorporation of Hindered Amine Light Stabilizers for Potential Applications in Flexible Optoelectronics

Abstract: Optically transparent polymer films with excellent thermal and ultraviolet (UV) resistance have been highly desired in advanced optoelectronic fields, such as flexible substrates for photovoltaic devices. Colorless and transparent polyimide (CPI) films simultaneously possess the good thermal stability and optical transparency. However, conventional CPI films usually suffered from the UV exposure and have to face the deterioration of optical properties during the long-term service in UV environments. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…CPIs are very important in various applications, such as optoelectronic devices, active-matrix organic light-emitting display devices (AMOLEDs), touch sensors, printed circuit boards (PCBs), thin-film transistors (TFTs), and solar cells [ 51 , 52 ]. Furthermore, the AMOLED displays of mobile electronic devices, such as smartphones and tablet PCs, are expected to be continuously improved in terms of visibility, durability, weight, and flexibility; consequently, CPIs have attracted significant amounts of academic and industrial research attention [ 53 , 54 ]. Recent research has demonstrated that adding specific structures to the main chain of PIs, such as fluorinated groups, alicyclic-group-containing monomers, noncoplanar structures, meta-substituted structures, or sulfones, can increase the transparency of PI films while lowering CTC formation [ 55 ].…”
Section: Pis For 5g/6g Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CPIs are very important in various applications, such as optoelectronic devices, active-matrix organic light-emitting display devices (AMOLEDs), touch sensors, printed circuit boards (PCBs), thin-film transistors (TFTs), and solar cells [ 51 , 52 ]. Furthermore, the AMOLED displays of mobile electronic devices, such as smartphones and tablet PCs, are expected to be continuously improved in terms of visibility, durability, weight, and flexibility; consequently, CPIs have attracted significant amounts of academic and industrial research attention [ 53 , 54 ]. Recent research has demonstrated that adding specific structures to the main chain of PIs, such as fluorinated groups, alicyclic-group-containing monomers, noncoplanar structures, meta-substituted structures, or sulfones, can increase the transparency of PI films while lowering CTC formation [ 55 ].…”
Section: Pis For 5g/6g Applicationsmentioning
confidence: 99%
“…Recent research has demonstrated that adding specific structures to the main chain of PIs, such as fluorinated groups, alicyclic-group-containing monomers, non-coplanar structures, meta-substituted structures, or sulfones, can increase the transparency of PI films while lowering CTC formation [55]. research attention [53,54]. Recent research has demonstrated that adding specific structures to the main chain of PIs, such as fluorinated groups, alicyclic-group-containing monomers, noncoplanar structures, meta-substituted structures, or sulfones, can increase the transparency of PI films while lowering CTC formation [55].…”
Section: Optical Transparencymentioning
confidence: 99%
“…Among various CPI films, the ones based on the alicyclic dianhydrides and aromatic diamines, that is, the semi-alicyclic (or semi-aromatic) systems, have attracted great attention in the research and development of high-performance polymers for optoelectronic applications due to the excellent combined thermal, optical, mechanical, and dielectric properties and the relatively low cost at the same time [ 13 , 14 , 15 , 16 ]. Various methodologies based on the molecular design of the functional alicyclic dianhydride or the aromatic diamine monomers have been proposed and carried out to reduce the CTE values of the semi-alicyclic CPI films.…”
Section: Introductionmentioning
confidence: 99%
“…Among various CPI films, the ones based on the alicyclic dianhydrides and aromatic diamines, that is the semi-alicyclic (or semi-aromatic) systems have attracted great attentions in the research and development of high-performance polymers for optoelectronic applications due to the excellent combined thermal, optical, mechanical and dielectric properties and the relatively low cost at the same time [13][14][15][16]. Various methodologies based on the molecular design of the functional alicyclic dianhydride or the aromatic diamine monomers have been proposed and carried out to reduce the CTE values of the semi-alicyclic CPI films.…”
Section: Introductionmentioning
confidence: 99%